Hospitalitas Dan Toleransi Otentik Dalam Relasi Antar Agama Di Belang - Manese, Rohit Mahatir (Ri'ayah: Jurnal Sosial dan Keagamaan, 2025)
This research aims to explore the occurrence of interfaith tolerance in Belang, Southeast Minahasa. until now there has never been interfaith division and friction. This research uses qualitative research methods to highlight the phenomenon of tolerance in Belang and to collect data using interview techniques, observation and documentation. To sharpen the data and facts, this research uses Jacques Derrida's hospitality theoretical framework. This study found that the cause of the creation of interreligious tolerance in Belang is influenced by interreligious marriages that foster an attitude of acceptance of diversity; The role of religious leaders who transmit knowledge and tolerant attitudes. This fact shows interreligious hospitality in Belang, Belang people are very inclusive of the emergence of others without devaluing and changing their existence. This means that inter-religions are open to each other and have a friendly attitude in social spaces. This research also found that the diverse community in Belang manifests religious teachings without interference, so that Christians and Confucians can worship and practice their respective religions safely; Celebrate together religious holidays; and sympathize when there are residents who mourn. This form of tolerance shows that tolerance in Belang is authentic. Tolerance is not just accepting and recognizing but having cohesiveness and interfaith collaboration.